EFFECTIVENESS OF DIABETES MELLITUS COUNSELING IN IMPROVING DIETARY COMPLIANCE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS : Ikhlasul Mumin, Egi Mulyadi, Amir Hamzah - Ikhlasul Mumin; Egi Mulyadi; Mustopa Saepul Alamsyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Type II diabetes mellitus is a chronic disease in which the pancreas does not produce enough insulin resulting in an increase in blood glucose levels above normal. The population in this study were 94 people with type II diabetes meatus. The sample needed is 40 patients. Data collection in this study was through distributing questionnaires and counseling. The data analysis used is descriptive statistical analysis and analysis using the t test. The results of data collection will go through several stages including validity test, reliability test, normality test, and homogeneity test. Based on the analysis of the t-test sample test, the results of statistical tests with the paired samples test showed a P-value value of 0.027 <0.05, which can be concluded that there is an effectiveness of diabetes mellitus counseling in improving diet compliance with type II diabetes mellitus